Clinical Evaluation of Oxidized Cellulose Powder and Endoscopic Applicator in Multicenter Trial - Petr Habal; Veronika Sívková; Zdeněk Šorm; Milan Chobola; Jiří Feix; Igor Slaninka; Jiřina Habalová; Tomáš Hosszú; Jaroslav Pacovský (Acta Medica)
Purpose: Oxidized cellulose-based haemostatic agents are widely used for managing bleeding in various surgical procedures. This study evaluates the efficacy and safety of oxidized cellulose powder and an endoscopic applicator across a broad spectrum of surgical settings. Methods: This was a prospective, multicentre study involving 99 evaluable patients undergoing surgeries with varying bleeding severities and surgical approaches (open, laparoscopic, or thoracoscopic). The primary endpoint was achieving haemostasis within 3 minutes and avoiding revision surgery within 12 hours. The time to haemostasis (TTH) and complications were recorded, and statistical comparisons were made using a paired and unpaired t-test, with a significance threshold of P < 0.05. Data from this study were compared to historical results from fibrillar haemostats. Results: Haemostasis was achieved within 3 minutes in 61.6% (95% CI [52.0, 71.2]) of patients and within 5 minutes in 99.0% (95% CI [97.0, 100.0]) of patients. The overall mean TTH was 153.8 seconds (95% CI: 141.5–166.1), with shorter TTH observed in minimally invasive procedures using the endoscopic applicator. Subgroup analysis revealed higher success rates for patients with mild bleeding (78%) compared to moderate bleeding (50%). Conclusion: Oxidized cellulose powder demonstrates reliable haemostatic performance across diverse surgical applications. The endoscopic applicator enhances precision and applicability, particularly in minimally invasive settings, making it a valuable tool in modern surgical practice.